2022
DOI: 10.3389/fphar.2022.1065289
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency ultrasound irradiation increases paclitaxel-induced sarcoma cells apoptosis and facilitates the transmembrane delivery of drugs

Abstract: Sarcoma is a malignant tumor derived from interstitial tissues and requires comprehensive treatment including chemotherapy. Paclitaxel (PTX) is an active agent against sarcoma, but its effect is not sufficiently acceptable and needs to be improved. Low-frequency ultrasound (LFU) has been documented to improve the efficacy of drugs by inducing reversible changes in membrane permeability; however, the effects of the combined use of LFU and PTX for sarcoma tumors remain unclear and warrant further investigation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…One strategy is focus on the development of paclitaxel nanocrystal formulation to improve the water solubility properties of this hydrophobic drug [ 42 ]. In another case, low-frequency ultrasound irradiation was used to improve the efficacy of paclitaxel to induce apoptosis of sarcoma cells [ 43 ]. Another strategy for solid tumor treatment has emerged using a novel extracellular matrix (ECM)-targeting nanotherapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy is focus on the development of paclitaxel nanocrystal formulation to improve the water solubility properties of this hydrophobic drug [ 42 ]. In another case, low-frequency ultrasound irradiation was used to improve the efficacy of paclitaxel to induce apoptosis of sarcoma cells [ 43 ]. Another strategy for solid tumor treatment has emerged using a novel extracellular matrix (ECM)-targeting nanotherapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that under the action of low-frequency ultrasound, the collapse process of MB caused by cavitation effect produces jets and releases energy, which can instantly rupture adjacent cell membrane, increase their permeability and promote the ingestion of drugs by cells ( Dong et al, 2017 ; Yang et al, 2018 ). At present, the way of using UTMD to improve the efficiency of drug targeting and delivery in local tissues is widely recognized in research ( Feril and Tachibana, 2012 ; Cai et al, 2022 ; Yang et al, 2022 ). Therefore, By combining ultrasound with microbubble therapy, tumor cells can be killed specifically, anti-tumor immune response can be stimulated, and tumor microenvironment can be improved, which is crucial for tumor immunotherapy ( Zhang et al, 2017 ).…”
Section: Overview Of Ultrasoundmentioning
confidence: 99%